2020
DOI: 10.1016/j.breast.2019.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of clinician-reported versus patient-reported outcomes of radiation dermatitis

Abstract: Radiation dermatitis is a common adverse effect of radiotherapy (RT) in breast cancer patients. Although radiation dermatitis is reported by either the clinician or the patient, previous studies have shown disagreement between clinician-reported outcomes (CROs) and patient-reported outcomes (PROs). This review evaluated the extent of discordance between CROs and PROs for radiation dermatitis. Studies reporting both clinician and patient-reported outcomes for external beam RT were eligible. Nine studies met the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 32 publications
1
21
2
Order By: Relevance
“…Thus, HFRT may minify the acute toxicity by decreasing the total dose. Breast induration is the possible outcome of advanced fibrosis following radiotherapy for breast cancer (48), and the possibility of breast fibrosis increased for 2 years after radiotherapy (49). It has been suggested that HFRT increases the incidence of fibrosis (34), but our data showed that the incidence of breast induration was improved in the HFRT group.…”
Section: Discussioncontrasting
confidence: 58%
“…Thus, HFRT may minify the acute toxicity by decreasing the total dose. Breast induration is the possible outcome of advanced fibrosis following radiotherapy for breast cancer (48), and the possibility of breast fibrosis increased for 2 years after radiotherapy (49). It has been suggested that HFRT increases the incidence of fibrosis (34), but our data showed that the incidence of breast induration was improved in the HFRT group.…”
Section: Discussioncontrasting
confidence: 58%
“…RR leads to cancer relapse, poor treatment response, poor prognosis, decreased quality of life, and increased disease treatment burden. Furthermore, RR induces damage to canceradjacent normal tissues, disrupting the physiological and biochemical functions of normal tissue, resulting in symptoms, including radiation-related diarrhea, rectal bleeding, and radiation dermatitis [39][40][41] , as well as an increased risk of subsequent secondary cancer 26,[42][43][44] or chronic noncommunicable diseases including type II diabetes 45,46 or cardiovascular diseases 47 . Over the past century, to remove the barrier of RR, many studies have been carried out to investigate RR-related regulatory genes, molecules, and signaling pathways to uncover the underlying mechanisms of RR and to develop radiation sensitizers 48,49 .…”
Section: Introductionmentioning
confidence: 99%
“…Both reported significantly less acute toxicity with patients treated with passively scattered proton therapy. As retrospective collection and physicianreported toxicities, in general, are limited in their ability to accurately reflect the true patient experience, [25][26][27] these data are the first to demonstrate improvement in patient treatment burden by prospectively acquired patient-reported toxicities as it correlates to dosimetric improvement with IMPT.…”
Section: Discussionmentioning
confidence: 99%